1998
DOI: 10.1007/s004240050757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carotid sinus nerve transection on changes in neuropeptide Y and indolamines induced by long-term hypoxia in rats

Abstract: Long-term hypoxia induces changes in neuropeptide-Y-like immunoreactivity (NPY-LI) and/or in the content of serotonin (5-HT) and its metabolite 5-hydroxyindoleacetic acid (5-HIAA) at the central level. To determine whether these alterations depend on the integrity of carotid body (CB) chemoreceptors, intact rats or those whose carotid sinus nerve was transected (CSNT) were exposed to hypoxia (10% O2) or to normoxia for 14 days. Thereafter, NPY-LI, 5-HT and 5-HIAA levels in discrete brain regions were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Several hypotheses could be raised to explain how acute or chronic hypoxia alters daily rhythms. First, carotid body chemoreceptors or ancillary central O 2 sensors, which may have a role in hypoxia-induced changes in basal level of neurotransmitters (23), could also be involved in the alteration of their daily rhythmicity. Local biochemical mechanisms could also be involved, especially through proteins such as hypoxiainducible factor 1 (HIF-1) (33), which may interact with the expression of genes regulating circadian rhythms (11,32).…”
Section: R71mentioning
confidence: 99%
See 1 more Smart Citation
“…Several hypotheses could be raised to explain how acute or chronic hypoxia alters daily rhythms. First, carotid body chemoreceptors or ancillary central O 2 sensors, which may have a role in hypoxia-induced changes in basal level of neurotransmitters (23), could also be involved in the alteration of their daily rhythmicity. Local biochemical mechanisms could also be involved, especially through proteins such as hypoxiainducible factor 1 (HIF-1) (33), which may interact with the expression of genes regulating circadian rhythms (11,32).…”
Section: R71mentioning
confidence: 99%
“…Indeed, catecholamine and indolamine metabolism, as well as the concentration of some neuropeptides, are altered in discrete brain areas during chronic hypoxia in the rat (22,24,25,30). Furthermore, some of these neurochemical alterations may be linked to the chemoreflex activation and the sympathetic hyperactivity that are known to be present in long-term hypoxic animals (23,30).…”
mentioning
confidence: 99%
“…It was demonstrated that hypoxia decreased the circulating levels of serotonin (the precursor of melatonin) by about 30% in different regions of the brain in rats, which would certainly influence the levels of melatonin and, thereby, its effect on cardiovascular system [20,22]. Despite a large volume of work on melatonin, its role in the cardiovascular system, particularly under hypoxic conditions, is poorly understood and its effect on hypoxic pulmonary hypertension has not been studied before.…”
Section: Introductionmentioning
confidence: 97%
“…Long-term hypoxia has been demonstrated to alter the brain indoleamine concentrations [20] and have an inhibitory effect on melatonin secretion [21]. It was demonstrated that hypoxia decreased the circulating levels of serotonin (the precursor of melatonin) by about 30% in different regions of the brain in rats, which would certainly influence the levels of melatonin and, thereby, its effect on cardiovascular system [20,22].…”
Section: Introductionmentioning
confidence: 98%